D'cheap Hardware Supplier Sdn. Bhd. / Khairul Hakkim Mohamad ... [et al.] - Mohamad, Khairul Hakkim; Mohari, Mohd. Amran; Yep, Mohd. Sallehuddin; Daud, Muhammad Adam; Mohd Yusof, Mohd Faizal; Mohd Dislan, Mohd Zahid (Malaysian Entrepreneurship Development Centre (MEDEC), 2001)
Every business or company have a strategic location for their business to get a good marketing and become successful. Among the location that is chosen the location that have a big potential for the business. Usually they choose location near to the industry area and accommodation area. It is because the location is near to the people. So that the business would become successful due to it have a big probability that customer coming to the premise.